Projeto e simulação de um micro inversor conectado a rede elétrica para conversão e injeção de energia fotovoltaica - Nakaya, Arthur Gonçalves (2022)
This work presents a study of a Micro Inverter for systems of generation and injection of energy from photovoltaic arrays using power electronics circuits, in converters of Boost CC-DC design, connected in cascade, four arrays in parallel, and full-fledged DC-AC converters. Bridge injecting power into the AC transmission grid. The converters are controlled using a Proportional-Integral controller. All the theoretical work was developed, later, specifications were defined for the project and simulations were carried out to prove the results.